The relationship between compensation factors and job satisfaction of employees - Agnes, Wong Su Su. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The aim of conducting this study was to determine the level of job satisfaction among employees and the compensation factors contributing to the job satisfaction among employees employed in selected g overnment sector in Sibu, Sarawak. A survey methodology using questionnaires with fiveApoint likert scale was used in this study. A total of 60 respondents were selected from the population of 135 as a sample of this study. Data analyses involved were the descriptive statistics (frequency and percentage) and inferential statistics using Statistical Package for the Social Science (SPSS). Descriptive statistics were used to describe the respondents’ selected demographics characteristics and the level of job satisfaction. Inferential statistics such as Pe arson Correlation Coefficient, TA test, TwoAway ANOVA, and Simple Regression Analysis were used to analyze the data.Result showed that employees had a high level of jo b satisfaction. The Pearson Correlation Test showed that there was a significant relationship (p< 0.01) between the compensation factors (base salary, allowances, interesting job duties, recognition) and employee’ job satisfaction. TAtest was used to evaluate the significant difference between male and female in term of their job satisfaction. The finding indicates that the male and female respondents at the organization have no difference in their job satisfaction. The finding from the TwoAway ANOVA test showed that there was no significant difference between the employees of various education levels in term of their job satisfaction. Besides, based on the result of Simple Regression Analysis, base salary is the most dominant factor contributing to the employees’ job satisfaction. Thus, the researcher suggests that advance actions can be taken to improve the four compensation factors in government sector in order to maintain job satisfaction among employees.